2008
DOI: 10.1155/2008/698759
|View full text |Cite
|
Sign up to set email alerts
|

Templated Fabrication of InSb Nanowires for Nanoelectronics

Abstract: Among various ways to produce nanowires, anodic alumina membrane- (AAM-) based synthesis has constantly received much attention, because AAM has a uniform and parallel porous nanostructure which makes it an ideal template material for fabricating highly ordered nanostructures. In this paper, we report fabrication of InSb nanowire arrays with diameter of 200 nm and 30 nm by direct current electrodeposition inside the nanochannels of anodic alumina membranes without subsequent annealing. The nanowires have four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…No other crystalline impurities peaks, such as In2O3, were detected in the XRD pattern. Similar XRD pattern has been reported earlier for electrochemically grown InSb nanowires [35][36][37].…”
Section: Semiconductors -Growth and Characterizationsupporting
confidence: 88%
“…No other crystalline impurities peaks, such as In2O3, were detected in the XRD pattern. Similar XRD pattern has been reported earlier for electrochemically grown InSb nanowires [35][36][37].…”
Section: Semiconductors -Growth and Characterizationsupporting
confidence: 88%
“…1,2) Generally, the addition small quantity of indium has the effect of hardening, strengthening, and increasing the corrosion resistance of the metal. Some indium alloys such as InSb, [3][4][5][6] InP, 7,8) InN, 9,10) InGaAs, 11) InSe 12) are studied as optoelectronic materials, magneto resistive materials and anodic materials of lithium battery. Indium oxide is used as transparent conducting materials in the form of Sn-doped In 2 O 3 (indium tin oxide, ITO).…”
Section: )mentioning
confidence: 99%
“…47,48) Electrodepositions of InSb were carried out at potentials of −0.65 to −1.55 V vs. SCE and at room temperature. Ortega and Herrero 41) obtained the polycrystalline fcc InSb that was free of In and Sb phases at −0.85 V vs. SCE.…”
Section: )mentioning
confidence: 99%
“…A molar ratio of In 3+ to Sb 3+ of 1.5±0.1 in the electrolyte yielded a deposit with an atomic ratio of In to Sb of 1.0±0.1. Khan et al 48) reported the fabrication of InSb nanowire arrays with diameters of 200 nm and 30 nm by electrodeposition at −1.5 V vs. Ag/AgCl inside the nanochannels of Au-sputtered anodic alumina membranes (AAM).…”
Section: )mentioning
confidence: 99%